Characteristics of NH3/H2 blend as carbon-free fuels: A review - Awad, Omar I.; Zhou, Bo; Harrath, Karim; Kadirgama, Kumaran (Elsevier Ltd, 2023)
In the pursue of a carbon-free economy, the utilization of fuels with low or zero carbon footprint account for only 1% of global final energy demand, a share that is predicted to follow a dramatic growth to 20% by 2050. Ammonia (NH3) has become dominant in the international transportation and storage of low-carbon alternative fuels. NH3 is regarded as an alternative fuel, as a carbon-free fuel, and renewable hydrogen (H2) carrier with high energy density, and its production and distribution infrastructure are well established. However, a current challenge is that NH3 has a lower burning velocity and a narrow flammability limit. Thus, the use of NH3 has numerous limitations in practical combustion applications. Blending NH3 with H2 is considered a solution that has been proposed to enhance NH3 combustion by improving ignition, flammability, and H2 safety issue. Using NH3 blended with H2 as a fuel in combustion systems is a practical approach to decarbonizing the energy sector. Thus, this review highlights the existing influential studies and ongoing research on NH3/H2 blended fuels. The review covers NH3 assists the safety behaviour of H2 use, in-situ NH3 dissociation, NH3 and H2 properties, NH3/H2 combustion characterization, techniques for low NOx NH3/H2 combustion, and challenges for NH3/H2 combustion. Finally, recommendations for future studies are provided for further developing the utilization of NH3/H2 as blended fuel.